The Impact of Reading Qur'an Verses in the Manaqib Kubra by Sheikh Abdul Qodir Jailani in Karangrejo Metro Lampung - Khoirunnisa; Muhammad Irsad; Eka Prasetiawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The activity of manaqib kubra in Karangrejo Metro Lampung has become a routine religious activity that has its own influence on its congregation. This shows that there is an atsar for the surrounding community through manaqib kubra activities in Karangrejo, Metro, Lampung. This study aims to explore the impact of the reading of Qur'anic verses on the activities of manaqib kubra by Sheikh Abdul Qodir Jailani in the book of Nurul Burhan. This study is qualitative with the living qur'an approach of Ahmad Rafiq's theory. The theory of living qur'an in this study uses functional reception. The data collection technique used semi-structured interview, observation and documentation methods. The data validity technique uses the Milles and Huberman model triangulation approach. The results of the study say that the recitation of Qur'an verses in Sheikh Abdul Qodir Jailani's manaqib kubra activity has a cultural impact and value. First, positive impacts such as providing peace of mind and mind so as to foster the spirit of carrying out worship as a form of piety to Allah and smoothing all affairs. Second, it has local cultural values in the implementation of dhikr and prayer using the local Javanese language, tolerance, strengthening friendship, strengthening spiritual values, the presence of food serving that shows acculturation between Islam and local culture and the use of tambourine when chanting prayers so as to increase love for Rosullulah.